EDUKASI CERDAS DAN BIJAK MENGGUNAKAN MEDIA SOSIAL BAGI SISWA SMAS AL-KAUTSAR PARUNGPANJANG - Debby Rahadian Baskhara; Cholis Hanifurohman; Rengga Herdiansyah (Abdi Jurnal Publikasi, 2025)
This Community Service Activity (PKM) was carried out at AL-Kautsar Parung Panjang High School with the theme “Smart and Wise Education Using Social Media”. The main objective of this activity is to improve students' ability to utilize social media positively and productively as a learning tool. Through this activity, students are given training and understanding of the use of social media platforms such as Instagram, YouTube, and WhatsApp in supporting the teaching and learning process. The methods used in this activity include lectures, group discussions, and hands-on practice. The results of this activity show that students are able to create educational content, interact effectively in online learning groups, and access and utilize digital learning resources more optimally. In addition, teachers are also provided with assistance in integrating social media into their learning curriculum. The positive impact of this activity can be seen from the increased interest and motivation of students in learning as well as the improvement of digital skills that are relevant to the needs of the times. This activity is expected to be a model for other schools in optimizing the use of social media as an effective and innovative learning tool.